2022
DOI: 10.1038/s41598-022-25979-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV infection and integrase strand transfer inhibitors-based treatment on the gut virome

Abstract: Viruses are the most abundant components of the human gut microbiome with a significant impact on health and disease. The effects of human immunodeficiency virus (HIV) infection on gut virome has been scarcely analysed. Several studies suggested that integrase strand transfers inhibitors (INSTIs) are associated with a healthier gut. Thus, the objective of this work was to evaluate the effects of HIV infection and INSTIs on gut virome composition. 26 non-HIV-infected volunteers, 15 naive HIV-infected patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…Contrary to the results observed in our previous works focused on gut microbiota [23,24], the effects of HIV infection and INSTIs on oral microbiota seem to be not very signi cant, probably due to the modulation of other factors such as smoking, and the greatest outward exposure of the oral cavity.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the results observed in our previous works focused on gut microbiota [23,24], the effects of HIV infection and INSTIs on oral microbiota seem to be not very signi cant, probably due to the modulation of other factors such as smoking, and the greatest outward exposure of the oral cavity.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous works from our group demonstrated that ARTs based on integrase strand transfer inhibitors (INSTIs) were associated with levels of systemic in ammation, bacterial translocation, and microbial diversity similar to those observed in uninfected controls [22]. Besides, these studies showed a clear impact of HIV-infection and INSTIs-based treatments on gut bacteriome [23] and virome [24]. However, how long-term ART, and speci cally INSTIs, modulate oral microbiota in HIV-infected patients and the implications of these effects on health deserve further research.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…This increased level of lysogenic phages remained even after treatment with integrase strand transfer inhibitors (INSTIs). [78] Liver cirrhosis Humans Patients with liver cirrhosis showcased prevalent levels in Siphoviridae, Podoviridae, and Myoviridae.…”
Section: Metabolic Syndrome (Mets) Humansmentioning
confidence: 99%